Experimentelle Untersuchungen und Bemessungsansätze für faserverstärktes Mauerwerk unter Erdbebenbeanspruchungen - Urban, Christian Moritz (Karlsruher Reihe Massivbau, Baustofftechnologie, Materialprüfung / Institut für Massivbau und Baustofftechnologie ; Materialprüfungs- und Forschungsanstalt Karlsruhe, 2015)
Several experimental campaigns are conducted to find feasible fiber reinforcements for buildings under earthquake conditions. Therefore tensile tests for the description of the bonding behavior of the fibers, shear tests on three-stone small specimen, small static cyclic shear wall tests, bending tests of wall segments, large format dynamically loaded wall plates and five building experiments were performed under realistic time history acceleration. At the end a calculation method is proposed.